RECOMENDACIONES INTERSOCIEDADES PARA DIAGNÓSTICO, TRATAMIENTO Y PREVENCIÓN DE LAS INFECCIONES POR CLOSTRIDIOIDES DIFFICILE. - Barcán, Laura; Martínez, Jorge Victor; Ducatenzeiler, Laura (Revista Medicina)
Intersociety guidelines for diagnosis, treatment and prevention of Clostridioides difficile infections. Clostridioides difficile infections (CDI) are among the leading causes of health care-associated infections. The epidemiology of CDI has undergone major changes in the last decade, showing an increase in incidence, severity, and rate of relapse. These guidelines were developed by specialists from four scientific societies: Sociedad Argentina de Infectología (SADI), Sociedad Argentina de Gastroenterología (SAGE), Sociedad Argentina de Bacteriología, Micología y Parasitología Clínicas (SADEBAC) and Asociación de Enfermeras en Control de Infecciones (ADECI). The objective of these intersociety guidelines is to provide national recommendations on CDI diagnosis, treatment and prevention. The methodology used involved the systematic review of the bibliography available up to December 2018, which was performed by six groups formed ad hoc: Epidemiology, Diagnosis, Treatment, Fecal Microbiota Transplantation, Special Populations, and Infection Control. The conclusions were presented and discussed in meetings held by each individual group and plenary meetings. In this document, updated diagnosis algorithms, therapeutic options (including fecal microbiota transplant) for immunocompetent and immunocompromised patients are presented, as well as strategies for the control of C. difficile infection.